MiRNA-194 activates the Wnt/β-catenin signaling pathway in gastric cancer by targeting the negative Wnt regulator, SUFU. (28th January 2017) - Peng, Yin; Zhang, Xiaojing; Ma, Qiang; Yan, Ruibin; Qin, Ying; Zhao, Yanqiu; Cheng, Yulan; Yang, Mengting; Wang, Qixiang; Feng, Xianling; Huang, Yong; Huang, Weiling; et al.
Abstract: Emerging evidence has shown that miRNA-194 is aberrantly upregulated in gastric cancer (GC); however, the biological mechanisms underlying its involvement are largely unknown. Wnt/β-catenin signaling has been implicated in gastric tumorigenesis; we therefore hypothesized that miRNA-194 promotes gastric carcinogenesis by activating Wnt/β-catenin signaling. MiRNA-194 was found to be overexpressed in GC cell lines and 43 paired GC tissues. Overexpression of miRNA-194 promoted cell proliferation and migration, while inhibition of miRNA-194 blocked these processes. Inhibition of miRNA-194 decreased tumor volumes in nude mice. Furthermore, miRNA-194 inhibitors promoted cytoplasmic localization of β-catenin, leading to repression of Wnt signaling. We also discovered that SUFU, a known negative regulator of Hedgehog and Wnt signaling, was a target of miRNA-194. Anti-SUFU siRNAs rescued the inhibitory effects of miRNA-194 antagonists on cell proliferation and migration and on colony formation. We also found that SUFU expression was downregulated in GC tissues and cell lines and negatively correlated with miRNA-194 expression in primary GC tissues. Moreover, SUFU expression was negatively correlated with tumor stage, supporting its potential as a diagnostic or prognostic marker in GC. Taken together, these findings suggest that miRNA-194 is oncogenic and promotes GC cell proliferation and migration by activating Wnt signaling, at least in part, via suppression of SUFU. Highlights: miRNA-194 is oncogenic in GC. miRNA-194 activates Wnt/β-catenin signaling pathway. miRNA-194 targets SUFU in human gastric cancer cells. SUFU expression is downregulated and negatively associated with tumor stage in GC.